Implementasi Sistem Kontrol dan Monitoring Lampu Jarak Jauh Menggunakan Blynk API dan Micropython - Firman Abdillah; Muhammad Koprawi (The Indonesian Journal of Computer Science, 2024)
The issue with the remote access involved in the process of controlling and monitoring of electric lightings becomes an intriguing of a area to be further explored. IoT based remote control and monitoring system can be one of the solutions for this issue through the applications of ESP8266 as the main controller, PZEM-004T sensor to monitor the lighting's electricity, and a relay as the electrical switch for the lighting's contol. This system runs using Microphthon combined with Blynk. Also added into the system a web interface which utilizes Blynk API, thus enabling it to be accessed from all devices anywhere. The result showed that the system runs well. This study also showed that IoT technology can be applied in managing household appliances such as lightings.